PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, PROFITABILITAS DAN TIPE AUDITOR TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL (Studi empiris pada perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia tahun 2013-2016) - Fita Aprilian, 13.05.52.0178; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2017)
This study aims to examine the effect of firm size, firm age, profitability and type of auditor to intellectual capital disclosure. This research use independent variable that is company size, company age, profitability and auditor type. While the dependent variable is the disclosure of intellectual capital. The population in this study are property and real estate companies listed on Indonesia Stock Exchange 2013-2016. The sample was chosen using purposive sampling method and obtained 158 samples of property and real estate companies. The method of analysis used in this study is multiple regression analysis with SPSS version 21 for windows. This study proves that firm size influences intellectual capital disclosure, auditor type has an effect on intellectual capital disclosure, firm age does not fall to intellectual capital disclosure, and profitability does not fall to intellectual capital disclosure.Keywords: Intellectual Capital Disclosure, Company Size, Company Age, Profitability, Audit Type